EFEKTIFITAS PEMBERIAN TEMULAWAK MADU TERHADAP PENINGKATAN NAFSU MAKAN PADA BALITA DENGAN GIZI KURANG DI DESA SOLOKAN WILAYAH KERJA PUSKESMAS PAKISJAYA KABUPATEN KARAWANG - Musmundiroh, Mus Mundiroh; Rohmah, Hajar NF; Walidah, Winna; Sriwadah, Supyati (Jurnal Delima Harapan, 2025)
Background: This study was conducted because many toddlers have problems with appetite. This study aims to examine the effect of giving temulawak honey on increasing appetite in undernourished toddlers. This research is a causality type with quantitative quasi-experiment research methods. The collection tool used is the CEBQ questionnaire. The target population is toddlers with malnutrition in Solokan Village, Pakisjaya, Karawang. The research subjects consisted of 42 undernourished toddlers, obtained using total sampling. The variables used in this study were the provision of temulawak honey as an independent variable and an increase in appetite for toddlers with malnutrition as a dependent variable. Measurement of variables using one group pretest-post test. Data analysis using bivariate analysis and unvariate analysis. The results of this study indicate that there is a significant difference between the appetite of toddlers before given temulawak honey and after given temulawak honey. This is evidenced by the number of toddlers with good appetite increased, namely before giving temulawak honey by 9.5%, while after being given temulawak honey the number of toddlers with good appetite amounted to 83.3%. From the results of this study it can be seen that temulawak honey can be used as an alternative to improve the appetite of toddlers, so that feeding in toddlers can be optimal